Modelagem da variação horária da temperatura do ar em Petrolina, PE, e Botucatu, SP - Ramos, Clovis M. C. [UNESP]; da Silva, Alessandra F. [UNESP]; Sartori, Anderson A. da C. [UNESP]; Zimback, Célia Regina Lopes [UNESP]; Bassoi, Luís Henrique [UNESP] (Universidade Federal da Paraíba (UFPB) Ccsa, 2011)
The air temperature is a climatic element of interest for several agricultural related studies. Hence, daily air temperature from two locations in Brazil (Botucatu and Petrolina, with different climate classification), hourly recorded from January 2004 to December 2005, were analysed to verify if 24 h long air temperature variation can be predicted with 6 h interval records. Three data set were selected, with different first time record of air temperature, and analyses performed using geoestatistics to confirm the temporal dependency of records. Then, ordinary krigging was used to model air temperature variation within 1 h interval, and spherical model presented the best approach, with range of 11.6 h for Botucatu and 12.7 for Petrolina. For both locations, the time of air temperature recording was the most importnat factor on accuracy of estimation of air temperature variation. Records at 2, 8, 14 and 20 h and at 4, 10, 16 and 22 h presented the best approaches, but for records at 9, 15 and 21 h, the approach was worst.

A temperatura do ar é um elemento climático de interesse para diversos estudos relacionados à produção agrícola. A partir de dados de temperatura do ar de Botucatu, SP, e Petrolina, PE (diferentes classificações climáticas), medidos entre janeiro de 2004 e dezembro de 2005, foram selecionados dados pontuais com intervalos de seis horas entre cada observação para cada dia. Desta forma, foram analisados três conjuntos de dados, variando a hora do primeiro registro, utilizando a técnica de geoestatística com o intuito de verificar e quantificar o grau de dependência temporal entre as observações. Comprovada a dependência temporal, o método da krigagem ordinária foi utilizado a fim de modelar a variação da temperatura do ar com o intervalo de uma hora. A análise geoestatística demonstrou a dependência temporal com ajuste ao modelo esférico, em ambas as localidades, (alcance de 11,6 h para Botucatu e 12,7 h para Petrolina). Para ambas as localidades o horário de medida da temperatura do ar, foi fator importante na exatidão de estiamtiva da variação da temperatura. Os registros às 2, 8, 14 e 20 h e às 4, 10, 16 e 22 h, geraram modelos com melhor desempenho, os modelos baseados nos registros às 9, 15 e 21 h, mostraram desempenho inferior.
Modeling the hourly variation of air temperature at Petrolina and Botucatu, Brazil
Keywords: geoestatistics; temporal dependency; climatic element